Considerations in addressing the opioid epidemic and chronic pain within the USA. (25th February 2019) - Marshall, Blaine; Bland, Michelle K; Hulla, Ryan; Gatchel, Robert J
This article reviews the complexities of the opioid epidemic, considering recent research involving the current state of the opioid epidemic; chronic pain and its role in the crisis; the properties of opioids and how they interact with human neurobiology; the effectiveness and risks of opioids as a treatment for chronic pain; opioid addiction and dependence; and pharmacological and psychological interventions for opioid addiction, opioid dependence, and chronic pain management. Opioid abuse can be reduced with the availability and access to treatment facilities for opioid detoxification; using interdisciplinary treatment models for chronic pain, opioid addiction and dependence; conducting more research in the areas of opioid addiction and opioid dependence; and shifting to an increase in nonpharmacological, less invasive treatments for pain.